ANALISIS FAKTOR YANG MEMPENGARUHI PENDAPATAN MASYARAKAT DI KABUPATEN MALANG TAHUN 2018-2022 - Wulandari, Vita Eka; Maryunani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The income of the population of a society is important for welfare because it influences its ability to meet basic needs. In Malang Regency there are around 2,685,900 people with a GDP per capita of 43.73 million rupiah in 2022. This research applies a quantitative approach. The research results show that the Covid-19 pandemic, rising fuel prices, low levels of education, people's mindsets that care less about education, economic limitations, lack of employment opportunities, and climate conditions are the causes of the high number of poor people, low levels of education, and low levels of poverty. high open unemployment. The impact is an increase in crime, limited access to education, high levels of unemployment, poverty, and a decline in prosperous economic conditions. Apart from these factors, education has a significant influence on people's income. Community income is not significantly influenced by the number of poor people and the level of open unemployment. The Malang Regency Government has implemented various programs to overcome these challenges, including Indonesian Economic Heroes (PENA), creating opportunities for small and medium enterprises (MSMEs), the Malang Makmur equality education movement program (GERTAK Malang Makmur), the Smart Indonesia Card (KIP), labor-intensive programs, job training programs, and the Pre-Employment Card Program.